Evaluation of compressive properties of SLM-fabricated multi-layer lattice structures by experimental test and μ-CT-based finite element analysis. (5th May 2019) - Lei, Hongshuai; Li, Chuanlei; Meng, Jinxin; Zhou, Hao; Liu, Yabo; Zhang, Xiaoyu; Wang, Panding; Fang, Daining
Abstract: The influence of inherent imperfections should be systematically investigated to ensure the safety and utilization of additive manufacturing-fabricated multi-scale parts and structures. Herein, two different types of multi-layer lattice sandwich panels, BCC and BCCZ, are prepared by selective laser melting (SLM) using the AlSi10Mg material. X-ray micro-computed tomography (μ-CT) is employed to capture the realistic geometrical information of lattice struts. Based on the statistical characteristics, a novel finite element model is established, which considers the specific non-uniform distribution of geometrical imperfection. Uniaxial compressive tests are performed to evaluate the influence of defects and number of layers on the overall mechanical performance and energy absorption capability. The results reveal that the diameter deviation of struts is changed with the change of strut location and built angle. In terms of compressive modulus and initial crushing strength, the prediction results of the reconstruction model are consistent with experimental results as compared to the as-designed and statistical average models. The layer-by-layer crushing behavior is the main failure mode for the multi-layer lattice panels. With the increase of layers number, the densification strain and crash load efficiency increased, whereas the specific energy absorption gradually decreased due to the impact of boundary conditions and failure modes. Graphical abstract: Unlabelled Image Highlights: Investigated the compressive deformation and energy absorption characteristics of lattice panels with various layers. Employed μ-CT technique to capture and analyze the geometrical imperfections of SLM-fabricated multi-layer lattice structure. Proposed a novel finite element modeling method taking the distribution locations of defects into account. Analyzed the influences of boundary conditions and failure modes on the energy absorption capability of lattice structures.